ANALYSIS OF SEPAK TAKRAW TRAINING PROGRAMS IN SMA NEGERI KEBERBAKATAN OLAHRAGA BENGKULU PROVINCE - Ice Trisna Wati; Martiani Martiani (Perkumpulan Dosen Muda Bengkulu, 2020)
This study aims to find out the implementation of sepak takraw training program by applying the tringulation method namely interview, observation and documentation study guidelines on athletes at SMA Keberbakatan Olahraga ofBengkulu Province. The type of research is a qualitative. The subjects of this study were 12 athletes at SMA Keberbakatan Olahraga of Bengkulu Province. Based on the results of the study , it can be concluded that the implementation of sepak takraw training program involves the coach directly. The coach provides training to athletes every Monday to Friday which is conducted twice a day, namely morning from 05:30 to 07:30 WIB and in the afternoon that is 16:00 to finish. Furthermore, the sepak takraw training program at SMA Keberbakatan Olahraga of Bengkulu Province has been programmed and continuous. This can be proven from the training program, training schedule and the coach who handle the training and implementation.